A high-smooth high-cleanliness ultra-light release film applied to high-end backlight die cutting and a preparation method thereof
Patent Information
- Application Number
- CN202611322770.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-20
AI Technical Summary
[0008]为了解决上述技术问题,本发明的目的是提供一种应用于高端背光模切的高平滑高洁净度超轻离型膜及其制备方法,以解决现有高端背光模切超轻离型膜存在的低洁净度、离型不良、剥离困难及胶层残留等问题
1、本发明基于现有技术的缺陷,开发了一款超轻高粘度无溶剂涂布配方,其特定的乙烯基长链结构,可实现低剥离力稳定性和残余性能的同步提升。同时由于大分子结构对于体系中硅粉微粒具有强包裹性,能够提供更强的抓取束缚力防止硅粉的团聚。而高粗糙PET原膜的选用,可以进一步降低硅粉的使用,从而提高膜面外观的致密均匀性和洁净度。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of release film technology, specifically to a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting and its preparation method. Background Technology
[0002] Release film refers to a thin film with a distinct surface, its main purpose being to achieve stable release force while ensuring the physical properties of the carrier film meet requirements. Based on the magnitude of the release force, it can be classified into light, medium, and heavy release films. In the manufacturing process of electronic or optical components, release film is a protective film used to prevent materials from sticking together. With the rapid development of smart electronic devices, more and more tapes used in the bezels of mobile phones, tablets, and other displays need to be die-cut into narrow shapes and bonded to ultra-thin substrates. Release films need to be used in conjunction with pressure-sensitive adhesives; the pressure-sensitive adhesive is first laminated with the release film, then die-cut, and finally enters the automatic or manual application process.
[0003] Existing high-end backlight die-cut ultralight release films face the following technical challenges: (I) Reverse Release Film Issue: This refers to the phenomenon where the release film, after being used with the composite material during production, peels off in reverse during use. Specifically, in backlight die-cutting, when peeling off the light film, the black adhesive that should be tightly adhered to the heavy film is peeled off along with it due to the reverse release film. This problem mainly arises because the release force of the release film increases significantly over time during storage after the pressure-sensitive adhesive is applied; this phenomenon is called "aging." Excessively aged release films can lead to reverse release, difficulty in peeling, and adhesive residue during customer use.
[0004] (II) Tack Reduction Issue: This refers to the varying degrees of decrease in adhesive strength after peeling off release films when using adhesive products. This significantly impacts downstream customer use. The problem primarily stems from excessive migratable substances (including unreacted active groups and free small molecules) in the release layer. During winding and lamination, these substances migrate to the back of the release film and the laminated pressure-sensitive adhesive, indirectly or directly damaging the adhesive's tack, leading to decreased adhesion and affecting subsequent bonding results. The industry has an indicator (residual adhesion rate) specifically for controlling the transfer of release substances from release films. Improving tack reduction mainly involves increasing the curing efficiency of the release film and limiting the presence of free small molecules.
[0005] (III) Surface Cleanliness: Backlight films are optical materials, requiring high surface cleanliness. Dust particles, dirt spots, and silicon powder particles from the production environment can adhere to the film surface, forming defects that manifest as bright or dark spots in display applications. To achieve lower release force while maintaining stability and minimal fluctuations, ultra-light release films in the industry typically increase the coating amount. While this results in a lighter release force, the thicker release layer inevitably leads to film stickiness, affecting downstream applications. Therefore, an anti-sticking agent (including fumed silica or silicon microspheres) must be added to the release formulation to prevent adhesion. This agent does not participate in the curing reaction of the release agent and exists in the release layer through physical mixing. If the silicon powder is poorly dispersed in the coating solution, the resulting ultra-light release film product is prone to silicon powder agglomeration and surface roughness, resulting in undesirable appearances. During the backlight die-cutting process, these silicon powder precipitates are very easy to transfer and fall off. If they are transferred to the backlight module, it will lead to the scrapping of the module product.
[0006] (iv) Oily / Smooth Film Surface Issues: Oiliness on the film surface occurs because the outer layer of the silicone oil coating cures better than the inner layer, allowing uncrosslinked silicone oil molecules and unevaporated solvent molecules to seep out, resulting in an oily release surface. A rough film surface is mainly caused by excessive release film coating or insufficient anti-sticking agent. Compared to products with a dry film surface, release films with an oily / smooth surface are prone to problems such as unstable peel force, difficulty in peeling, and reverse release during use.
[0007] Therefore, based on market needs and existing technological challenges, developing an ultra-lightweight release film with high smoothness and high cleanliness for high-end backlight die-cutting has significant market application value. Summary of the Invention
[0008] To address the aforementioned technical problems, the present invention aims to provide a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting and its preparation method, thereby solving the problems of low cleanliness, poor release, difficult peeling, and adhesive residue existing in current high-end backlight die-cutting ultra-light release films.
[0009] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: In a first aspect, the present invention provides a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting, comprising a substrate and a release layer coated on the surface of the substrate; The release layer comprises the following raw materials in parts by weight: 90-110 parts modified methyl vinyl siloxane, 1.0-3.0 parts crosslinking agent, 0.5-1.5 parts anchoring agent, 0.5-3.0 parts catalyst, 0.5-2.5 parts light release modifier, 0.5-2.5 parts anti-sticking agent, and 200-600 parts diluent.
[0010] Furthermore, the release layer comprises the following raw materials in parts by weight: 100 parts modified methyl vinyl siloxane, 2.2 parts crosslinking agent, 0.5 parts anchoring agent, 1.5 to 2.0 parts catalyst, 1.0 to 2.0 parts light release modifier, 0.5 to 2.0 parts anti-sticking agent, and 500 parts diluent.
[0011] Preferably, the release layer comprises the following raw materials in parts by weight: 100 parts modified methyl vinyl siloxane, 2.2 parts crosslinking agent, 0.5 parts anchoring agent, 2.0 parts catalyst, 2.0 parts light release modifier, 2.0 parts anti-sticking agent, and 500 parts diluent.
[0012] Furthermore, the substrate is an optical-grade high-roughness PET film with a thickness of 25~75 μm and an average roughness Ra of 0.15~0.2 μm.
[0013] The beneficial effects of adopting the above-mentioned further technical solution are as follows: This invention uses an optical-grade high-roughness PET film, which differs from conventional PET films (average roughness Ra is 0.05~0.08 μm). This high-roughness PET film is obtained by adding micro-protruding particles to the PET film layer. Due to the micro-protrusion structure composed of specific particles, a specific interlayer structure can be formed on the film surface, improving the surface roughness of the film material. At the same time, the increase in the surface roughness of the film material has a positive effect on the dryness and anti-adhesion effect of the film surface after silicone coating.
[0014] Furthermore, the modified methyl vinyl siloxane has an average viscosity of 10,000 to 15,000 cps and a solid content of 100%.
[0015] The beneficial effects of adopting the above-mentioned further technical solution are as follows: This invention uses modified methyl vinyl siloxane as a high-viscosity solvent-free release agent silicone oil. Due to its specific vinyl long-chain siloxane structure, there are sufficient reaction sites on the polymer chain. After curing, a dense three-dimensional cross-linked network can be formed, which can provide ultra-light and stable release force and maintain a sufficiently high residual adhesion rate. At the same time, the modified methyl vinyl siloxane contains inhibitors, so no additional addition is required.
[0016] Furthermore, the crosslinking agent is polymethylsiloxane.
[0017] The beneficial effects of adopting the above-mentioned further technical solution are as follows: the present invention uses polymethylsiloxane as a crosslinking agent. As a hydrogen-containing silicone oil, it can undergo an addition reaction with modified methyl vinylsiloxane under the action of thermal catalysis to form a crosslinked network with release properties.
[0018] Furthermore, the anchoring agent is a silane coupling agent containing silanol groups.
[0019] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: The present invention uses a silane coupling agent containing silanol groups as a "molecular bridge" to connect the organosilicon coating and the inorganic PET substrate, which can improve the problem of poor adhesion of organosilicon materials on the surface of inert PET substrate and achieve anchoring effect.
[0020] Furthermore, the catalyst is a platinum complex catalyst.
[0021] The beneficial effects of adopting the above-mentioned further technical solution are as follows: the platinum complex catalyst belongs to the Karstedt class of catalysts, which is formed by complexing chloroplatinic acid with vinyl-terminated siloxanes (such as tetramethyldivinyldisiloxane). It has high reactivity, stable storage, and a platinum content ≥5000 ppm.
[0022] Furthermore, the light release modifier is a reactive polysiloxane polymer.
[0023] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: the reactive polysiloxane polymer has a unique organosilicon structure and free radical polymerization characteristics, achieving a balance between low peel force and high residual adhesion.
[0024] Furthermore, the anti-sticking agent is an emulsion-type fumed silica.
[0025] The beneficial effects of adopting the above-mentioned further technical solution are as follows: By adding an appropriate amount of nano-sized silica particles to the coating liquid system, the present invention can effectively improve the smoothness of the film surface and prevent abnormal adhesion of the release film product to the release surface, thus affecting the use by downstream customers. At the same time, the surface-treated inorganic silica particles have excellent media dispersibility, which can effectively prevent the sedimentation and agglomeration of silica powder in the coating liquid during the coating process, thereby effectively improving the agglomerated silica powder points generated on the product film surface and improving the cleanliness of the film surface.
[0026] Furthermore, the diluent is a mixed solvent consisting of toluene, D120 gasoline and methyl ethyl ketone; the mass ratio of toluene, D120 gasoline and methyl ethyl ketone is (50~100):(200~350):(100~200).
[0027] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: By selecting the composition and ratio of the organic solvent system, the present invention enables it to have better solubility and dispersibility, which is conducive to the uniform dispersion of each raw material and better leveling performance.
[0028] Furthermore, the dry silicon coating amount of the release layer is 0.7~0.9 g / m. 2 .
[0029] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: the commonly used dry silicon coating amount in the prior art is 1.2~1.8 g / m². 2A higher coating amount results in a lighter release force, but this leads to a significant increase in production costs, making it unsuitable for mass production. Furthermore, an increased coating amount inevitably increases the proportion of anti-sticking agent in the formulation, making it difficult to guarantee product cleanliness. This invention, however, ensures that the release film provides a stable, ultra-light release force and a high residual adhesion rate with a lower coating amount, effectively reducing production costs.
[0030] A second aspect of the present invention provides a method for preparing the above-mentioned high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting, comprising the following steps: All raw materials for the release layer are mixed evenly to obtain a coating liquid; then the coating liquid is evenly coated on the surface of an optical-grade high-roughness PET film that has been corona-treated; finally, a thermosetting treatment is performed to obtain a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting.
[0031] Furthermore, the mixing method employs a customized stirring and circulating dispersion system, including a sawtooth stirring disperser, a circulating reflux device, and a three-stage filtration system.
[0032] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: the present invention uses a sawtooth stirring disperser, which has better shear dispersion performance, realizes uniform dispersion of silicon powder and prevents sedimentation; the circulating reflux device ensures coating stability and uniformity; and the three-stage filtration system further reduces the occurrence of silicon powder agglomeration and improves appearance quality.
[0033] Furthermore, the coating method adopts a micro-gravure coating process, and the mesh count of the micro-gravure roller is 180 mesh.
[0034] The beneficial effects of adopting the above-mentioned further technical solutions are: the film surface of the micro-concave process product is smoother and flatter, with no obvious processing lines.
[0035] Furthermore, process static elimination equipment is added at multiple locations such as the unwinding and winding and coating heads to control the winding voltage of the product.
[0036] Furthermore, the corona value of the optical-grade high-roughness PET film after corona treatment is 46~56 dynes.
[0037] Preferably, the corona value of the optical-grade high-roughness PET film after corona treatment is 56 dynes.
[0038] Furthermore, the heat curing temperature is 140~160℃, and the time is 0.5~2 min.
[0039] Preferably, the thermosetting temperature is 155°C and the time is 1 min.
[0040] The present invention has the following beneficial effects: 1. This invention addresses the shortcomings of existing technologies by developing an ultra-lightweight, high-viscosity, solvent-free coating formulation. Its specific vinyl long-chain structure enables simultaneous improvement in low peel strength stability and residual performance. Furthermore, the macromolecular structure provides strong encapsulation of silica powder particles within the system, offering enhanced binding force to prevent silica powder agglomeration. The use of a high-roughness PET film further reduces silica powder usage, thereby improving the density, uniformity, and cleanliness of the film surface.
[0041] 2. Thanks to the excellent release properties of the formulation of this invention, the release film can provide stable ultra-light release force and high residual adhesion rate with a relatively low coating amount, meeting the application requirements of downstream backlight die-cutting. Compared with the coating process of existing technologies, this invention can effectively reduce production costs.
[0042] 3. This invention strictly controls the on-site production process. By improving the cleanliness level, controlling static electricity in the process, and standardizing the operating procedures, the risk of contamination and defects can be effectively reduced, thus ensuring the stability and cleanliness of the product.
[0043] 4. The ultralight release film provided by this invention has been tested according to FINAT standards. The release force can be stabilized at 1.7~2.5 cN / 2.5 cm for 20 min, and the release force after 24 h of aging is 3.0~3.5 cN / 2.5 cm. The residual adhesion reaches 80% after 24 h. The winding voltage is less than 1 kV. The film surface has a good appearance, is delicate, dry, dense and uniform, has high cleanliness, and has no obvious defects such as silicon powder points or electrostatic damage, which can meet the needs of downstream backlight die-cutting production. Detailed Implementation
[0044] The principles and features of the present invention are described below with reference to embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, specific conditions or manufacturer-recommended conditions should be followed in the embodiments. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0045] Example 1: A high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting includes a substrate and a release layer coated on the surface of the substrate. The release layer comprises the following raw materials in parts by weight: 100 parts modified methyl vinyl siloxane (Shanghai Cyrosack GJ-01), 2.2 parts crosslinking agent (polymethyl siloxane, Shanghai Cyrosack JL-01), 0.5 parts anchoring agent (silane coupling agent containing silanol groups, Dow Corning Syl-off 9176), 1.5 parts catalyst (platinum complex catalyst, Dow Corning Syl-off 4000), 1.0 part light release modifier (reactive polysiloxane polymer, Shanghai Zhongboli QB002), 0.5 parts anti-sticking agent (emulsion-type fumed silica, KCC-SL3000), and 500 parts diluent (composed of 100 parts toluene, 200 parts D120 gasoline, and 200 parts methyl ethyl ketone). The substrate is an optical-grade high-roughness PET film (Dongcai GM49) with a thickness of 50 μm and an average roughness Ra of 0.18 μm.
[0046] The above-mentioned method for preparing a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting includes the following steps: S1. Preparation of release agent Modified methyl vinyl siloxane was added to a diluent consisting of toluene, D120 gasoline and methyl ethyl ketone, and stirred thoroughly for 10 min. Then, crosslinking agent, anchoring agent, catalyst, light release modifier and anti-sticking agent were added in sequence, and the mixture was stirred evenly in a mixing tank for 15 min to obtain the release agent.
[0047] S2, Substrate Pretreatment Optical-grade, high-roughness PET films are subjected to corona treatment to achieve a corona value of 56 dynes.
[0048] S3, Coating Curing Using a micro-gravure coating process, the release agent obtained from S1 is uniformly coated on the surface of a PET film after corona treatment, and then heat-cured at 155℃ for 1 min to obtain a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting. The release agent is stirred, circulated, dispersed, and filtered before use, and static electricity is controlled in the on-site process.
[0049] Example 2: A high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting includes a substrate and a release layer coated on the surface of the substrate. The release layer comprises the following raw materials in parts by weight: 100 parts modified methyl vinyl siloxane (Shanghai Cyrosack GJ-01), 2.2 parts crosslinking agent (polymethyl siloxane, Shanghai Cyrosack JL-01), 0.5 parts anchoring agent (silane coupling agent containing silanol groups, Dow Corning Syl-off 9176), 2.0 parts catalyst (platinum complex catalyst, Dow Corning Syl-off 4000), 1.5 parts light release modifier (reactive polysiloxane polymer, Shanghai Zhongboli QB002), 1.5 parts anti-sticking agent (emulsion-type fumed silica, KCC-SL3000), and 500 parts diluent (composed of 50 parts toluene, 350 parts D120 gasoline, and 100 parts methyl ethyl ketone). The substrate is an optical-grade high-roughness PET film (Dongcai GM49) with a thickness of 50 μm and an average roughness Ra of 0.18 μm.
[0050] The above-mentioned method for preparing a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting includes the following steps: S1. Preparation of release agent Modified methyl vinyl siloxane was added to a diluent consisting of toluene, D120 gasoline and methyl ethyl ketone, and stirred thoroughly for 10 min. Then, crosslinking agent, anchoring agent, catalyst, light release modifier and anti-sticking agent were added in sequence, and the mixture was stirred evenly in a mixing tank for 15 min to obtain the release agent.
[0051] S2, Substrate Pretreatment Optical-grade, high-roughness PET films are subjected to corona treatment to achieve a corona value of 56 dynes.
[0052] S3, Coating Curing Using a micro-gravure coating process, the release agent obtained from S1 is uniformly coated on the surface of a PET film after corona treatment, and then heat-cured at 155℃ for 1 min to obtain a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting. The release agent is stirred, circulated, dispersed, and filtered before use, and static electricity is controlled in the on-site process.
[0053] Example 3: A high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting includes a substrate and a release layer coated on the surface of the substrate. The release layer comprises the following raw materials in parts by weight: 100 parts modified methyl vinyl siloxane (Shanghai Celosiac GJ-01), 2.2 parts crosslinking agent (polymethyl siloxane, Shanghai Celosiac JL-01), 0.5 parts anchoring agent (silane coupling agent containing silanol groups, Dow Corning Syl-off 9176), 2.0 parts catalyst (platinum complex catalyst, Dow Corning Syl-off 4000), 2.0 parts light release modifier (reactive polysiloxane polymer, Shanghai Zhongboli QB002), 2.0 parts anti-sticking agent (emulsion-type fumed silica, KCC-SL3000), and 500 parts diluent (composed of 50 parts toluene, 350 parts D120 gasoline, and 100 parts methyl ethyl ketone). The substrate is an optical-grade high-roughness PET film (Dongcai GM49) with a thickness of 50 μm and an average roughness Ra of 0.18 μm.
[0054] The above-mentioned method for preparing a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting includes the following steps: S1. Preparation of release agent Modified methyl vinyl siloxane was added to a diluent consisting of toluene, D120 gasoline and methyl ethyl ketone, and stirred thoroughly for 10 min. Then, crosslinking agent, anchoring agent, catalyst, light release modifier and anti-sticking agent were added in sequence, and the mixture was stirred evenly in a mixing tank for 15 min to obtain the release agent.
[0055] S2, Substrate Pretreatment Optical-grade, high-roughness PET films are subjected to corona treatment to achieve a corona value of 56 dynes.
[0056] S3, Coating Curing Using a micro-gravure coating process, the release agent obtained from S1 is uniformly coated on the surface of a PET film after corona treatment, and then heat-cured at 155℃ for 1 min to obtain a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting. The release agent is stirred, circulated, dispersed, and filtered before use, and static electricity is controlled in the on-site process.
[0057] Comparative Example 1: A release film includes a substrate and a release layer coated on the surface of the substrate; The release layer comprises the following raw materials in parts by weight: 100 parts of vinyl polysiloxane, 9 parts of hydrogen-containing polysiloxane, 12 parts of anchoring agent 3-glycidyl etheroxypropyltriethoxysilane, 3 parts of release force modifier 4-ethoxy-1,1,1-trifluoro-3-buten-2-one, and 10 parts of platinum catalyst. The substrate is a conventional PET film (average roughness Ra is 0.06 μm).
[0058] The above-mentioned method for preparing the release film includes the following steps: First, the release layer raw materials are mixed evenly to obtain a release agent. Then, the release agent is coated on one side of a conventional PET film and heat-cured to obtain a release film.
[0059] Comparative Example 2: An ultralight release film includes a substrate and a release layer coated on the surface of the substrate; The release layer comprises the following raw materials in parts by weight: 4.7 parts silica powder, 7.4 parts gasoline, 10.6 parts isopropanol, 1.6 parts vinyltriethoxysilane, 2.8 parts polyetherimide, 15.6 parts diatomaceous earth, 3.3 parts β-carboxyethyl acrylate, 7.5 parts styrene-acrylic emulsion, and 4.8 parts polyurethane; The substrate is a conventional PET film (average roughness Ra is 0.06 μm).
[0060] The preparation method of the above-mentioned ultralight release film includes the following steps: First, the release layer raw materials are mixed evenly to obtain a release agent. Then, the release agent is coated on one side of a conventional PET film and heat-cured to obtain an ultra-lightweight release film.
[0061] Experimental example: The release performance and appearance of different types of release films prepared in Examples 1-3 and Comparative Examples 1-2 were tested and evaluated. The release force was tested using TESA 7475 tape at 300 mm / min and 180°. The residual adhesion rate was tested using Nitto 31B tape at 300 mm / min and 180°. After the tape was applied to the release film, the original PET film was transferred onto it. The release performance stability of the release film prepared in Example 3 was tested.
[0062] The experimental results are shown in Tables 1 and 2.
[0063] Table 1. Test results of release performance and residual adhesion of release films in the examples and comparative examples.
[0064] Table 2. Results of time-dependent stability verification tests on release force in Example 3
[0065] As shown in Table 1, compared with Comparative Examples 1-2, the release films prepared in the embodiments of the present invention exhibit excellent release performance and good film surface appearance with significantly lower coating amounts. In the release films prepared in Examples 1-3, the release force stabilizes at 1.7-2.5 cN / 2.5 cm for 20 min, and the aging release force is 3.0-3.5 cN / 2.5 cm after 24 h. The residual adhesion rate reaches over 80% after 24 h, the winding voltage is less than 1 kV, and the film surface is delicate, dry, dense, uniform, and highly clean, without obvious defects such as silicon powder points or electrostatic damage, meeting the needs of downstream backlight die-cutting production. Among these, Example 3 is the optimal embodiment of the present invention, and this release film has a coating amount of 0.8 g / m³. 2 At the coating amount, the release force is only 1.8 cN / 2.5 cm after 20 min, and only 3.1 cN / 2.5 cm after 24 h of aging. The winding voltage is only 0.7 kV. After 25 days of room temperature and high temperature aging release performance stability test, the results showed that the release film still maintains excellent release performance and good stability.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting, characterized in that, Includes the substrate and the release layer coated on the surface of the substrate; The release layer comprises the following raw materials in parts by weight: 90-110 parts modified methyl vinyl siloxane, 1.0-3.0 parts crosslinking agent, 0.5-1.5 parts anchoring agent, 0.5-3.0 parts catalyst, 0.5-2.5 parts light release modifier, 0.5-2.5 parts anti-sticking agent, and 200-600 parts diluent.
2. The high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting as described in claim 1, characterized in that, The release layer comprises the following raw materials in parts by weight: 100 parts modified methyl vinyl siloxane, 2.2 parts crosslinking agent, 0.5 parts anchoring agent, 1.5 to 2.0 parts catalyst, 1.0 to 2.0 parts light release modifier, 0.5 to 2.0 parts anti-sticking agent, and 500 parts diluent.
3. The high-smoothness, high-cleanliness, ultra-lightweight release film for high-end backlight die-cutting as described in claim 1 or 2, characterized in that, The substrate is an optical-grade high-roughness PET film with a thickness of 25~75 μm and an average roughness Ra of 0.15~0.2 μm.
4. The high-smoothness, high-cleanliness, ultra-lightweight release film for high-end backlight die-cutting as described in claim 1 or 2, characterized in that, The modified methyl vinyl siloxane has an average viscosity of 10,000 to 15,000 cps and a solid content of 100%.
5. The high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting as described in claim 1 or 2, characterized in that, The crosslinking agent is polymethylsiloxane; The anchoring agent is a silane coupling agent containing silanol groups; The catalyst is a platinum complex catalyst; The light release modifier is a reactive polysiloxane polymer; The anti-sticking agent is an emulsion-type fumed silica.
6. The high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting as described in claim 1 or 2, characterized in that, The diluent is a mixed solvent consisting of toluene, D120 gasoline and methyl ethyl ketone; the mass ratio of toluene, D120 gasoline and methyl ethyl ketone is (50~100):(200~350):(100~200).
7. The high-smoothness, high-cleanliness, ultra-lightweight release film for high-end backlight die-cutting as described in claim 1 or 2, characterized in that, The dry silicon coating amount of the release layer is 0.7~0.9 g / m. 2 .
8. The method for preparing a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting according to any one of claims 1 to 7, characterized in that, Includes the following steps: All raw materials for the release layer are mixed evenly to obtain a coating liquid; then the coating liquid is evenly coated on the surface of an optical-grade high-roughness PET film that has been corona-treated; finally, a thermosetting treatment is performed to obtain a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting.
9. The method for preparing a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting according to claim 8, characterized in that, The corona value of the optical-grade high-roughness PET film after corona treatment is 46~56 dynes.
10. The method for preparing a high-smoothness, high-cleanliness, ultra-light release film for high-end backlight die-cutting according to claim 8, characterized in that, The thermosetting temperature is 140~160℃, and the time is 0.5~2 min.